2021
DOI: 10.1177/23743735211034047
|View full text |Cite
|
Sign up to set email alerts
|

Improving Communications With Patients and Families in Geriatric Care. The How, When, and What

Abstract: There has been little published literature examining the unique communication challenges older adults pose for health care providers. Using an explanatory mixed-methods design, this study explored patients’ and their family/caregivers’ experiences communicating with health care providers on a Canadian tertiary care, inpatient Geriatric unit between March and September 2018. In part 1, the modified patient–health care provider communication scale was used and responses scored using a 5-point scale. In part 2, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…This study illustrates a framework of “How” the healthcare team communicated, “When” they communicated, and “What” they communicated. ( 8 ) Our study demonstrates “How” HCPs communicated was important for OAs with responses that included terms such as active listener, attentive, thorough, and empathetic” descriptive of a “good provider”. They provided responses such as disengaged, hasty, neglectful, and lack of eye contact for “bad providers.”…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This study illustrates a framework of “How” the healthcare team communicated, “When” they communicated, and “What” they communicated. ( 8 ) Our study demonstrates “How” HCPs communicated was important for OAs with responses that included terms such as active listener, attentive, thorough, and empathetic” descriptive of a “good provider”. They provided responses such as disengaged, hasty, neglectful, and lack of eye contact for “bad providers.”…”
Section: Discussionmentioning
confidence: 80%
“…Like other studies, the themes from our study support improving patient-centered care and communication. ( 8 , 9 ) Huang and colleagues study evaluated how geriatric patients and their caregivers perceive HCP’s communication skills in an inpatient setting. This study illustrates a framework of “How” the healthcare team communicated, “When” they communicated, and “What” they communicated.…”
Section: Discussionmentioning
confidence: 99%
“…Potential solutions include providing older people and family members with a two‐way communication checklist of questions about discharge, which could help initiate conversations and help better prepare them 40 . More strategic use of written information and predischarge meetings focused on discharge assessments and what to expect after discharge have also been shown to improve shared decision‐making in geriatric inpatient care 41 …”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, Huang et al also reported inappropriate communication styles between the healthcare team and older adult patients. 37 Another study stated that older adult patients expect the healthcare team should primarily act based on the principles of good communication, take the concerns of older people into account, and share information and decisions with them. 38 …”
Section: Discussionmentioning
confidence: 99%